Women and Corruption: understanding women's perceptions of links between gender and corruption in South Africa - Motala, Sabeehah (My University, 2022)
The interaction between gender and corruption is a relatively unstudied area in South Africa, even though it is becoming more prominent in global anti-corruption work. As a starting point to research in this area, this dissertation explores women’s understanding of corruption and how they perceive it in relation to gender. It investigates how women define corruption; whether women view gender as correlating to levels of corruption; and whether women think that gender influences experiences of corruption in South Africa. Twelve women from various backgrounds were interviewed in order to answer these questions. The main conclusions drawn by this research are a proposed definition of corruption broad enough to acknowledge its interaction with other social processes to allow better study of it from a gendered perspective; that women in South Africa generally understand corruption as an immoral act with power as a central tenet determining how one participates in corruption, rather than being a man or a woman; that women perceive that gender constructions in the form of roles and dynamics play a part in how women experience corruption in South Africa; and ultimately a proposed intersectional theory of corruption.
A dissertation submitted in partia fulfilment of the requirement for the degree of Master of Arts in Sociology to the Faculty of Humanities, School of Social Science, University of the Witwatersrand, 2022